A Secure Cluster Formation Scheme in Wireless Sensor Networks. (15th October 2012) - Wang, Gicheol; Kim, Dongkyun; Cho, Gihwan
Abstract : In wireless sensor networks, clustering expedites many desirable functions such as load balancing, energy savings, and distributed key management. For secure clustering, it is very important to find compromised nodes and remove them during the initial cluster formation process. If some nodes are compromised and survive the censorship process, they can make some nodes have a different cluster view and can split a cluster into multiple clusters to deteriorate cluster quality as a whole. To resolve these problems, we propose a robust scheme against such attacks in this paper. First, our scheme generates large-sized clusters where any two nodes are at most two hops away from each other to raise the quality of clusters. Second, our scheme employs the verification of two-hop distant nodes to preserve the quality of the large-sized clusters and refrains from splitting the clusters. Last, our scheme prefers broadcast transmissions to save the energy of nodes. Security analysis proves that our scheme can identify compromised nodes and preserves the cluster membership agreement against the compromised nodes. In addition, simulation results prove that our scheme generates fewer clusters and is more secure and energy efficient than the scheme producing only small-sized clusters.